Cosmic Magnetic Fields - Beck, Rainer; Wielebinski, Richard (Lecture notes in physics, 2005)
While magnetic fields permeate the universe on all scales, the present book is dedicated to their investigation on the largest scales and affords a balanced account of both theoretical and observational aspects. Written as a set of advanced lectures and tutorial reviews that lead up to the forefront of research, this book offers both a modern source of reference for the experienced researchers as well as a high-level introductory text for postgraduate students and nonspecialist researchers working in related areas. TOC:Magnetic Fields in the Early Universe.- Observations of Magnetic Fields in the Distant Universe.- Magnetic Fields in Galaxies.- The Origin of Magnetic Fields.- Numerical Magnetohydrodynamics in Astrophysics.- Importance of Magnetic Helicity in Dynamos.- Magnetic Fields in the Milky Way From Radio Continuum and Faraday Rotation Studies.- Magnetic Fields in Diffuse HI and Molecular Clouds.- Stellar Magnetic Fields.- The Origin of the Global Magnetic Structure in the Milky Way
Keywords: Aufsatzsammlung; Interstellares Magnetfeld; Extragalaktisches Magnetfeld; Galaktisches Magnetfeld